Growth and spectral properties of Pr3+-doped Y3Al5O12 crystal for potential use in all-solidstate visible laser. (23rd February 2017) - Liu, Wenpeng; Zhang, Qingli
Abstract : Pr 3+ -doped Y3 Al5 O12 (Pr:YAG) single crystal has been grown by the Czochralski technique. The room temperature absorption spectrum, emission spectrum, and fluorescence decay curves of Pr:YAG single crystal were studied systematically. Strong absorption peaks in the blue region corresponding to 3 H 4 → 3 P 2, 1, 0  +  1 I 6 transitions and emission peaks in the visible region originating from the 3 P 1, 3 P 0 and 1 D 2 levels of Pr 3+ are observed. The emission cross-sections of four main promising laser transitions at 488, 566, 611 and 638 nm were estimated separately. Results show that Pr:YAG single crystal is an excellent candidate for all-solid-state visible laser material that can be pumped by blue laser diode.